Morchella importuna Polysaccharides Alleviate Carbon Tetrachloride-Induced Hepatic Oxidative Injury in Mice - Xu, Yingyin; Xie, Liyuan; Tang, Jie; He, Xiaolan; Zhang, Zhiyuan; Chen, Ying; Zhou, Jie; Gan, Bingcheng; Peng, Weihong (Frontiers in Physiology, 2021)
The present study aimed to investigate the effects of Morchella importuna polysaccharides (MIPs) on carbon tetrachloride (CCl4)-induced hepatic damage in mice. A total of 144 female mice were randomly assigned to four treatment groups: control, CCl4, low dose MIPs (LMIPs) group, and high dose MIPs (HMIPs) group. After the 10-day experiment, serum and liver were sampled for biochemical and metabolomic analyses. The HMIPs markedly decreased the liver weight under CCl4 intoxication. Furthermore, the significantly elevated concentration of five serum biochemical parameters, including alanine aminotransferase (ALT), aspartate aminotransferase (AST), triglyceride (TG), total cholesterol (TC), and total bile acid (TBA) under CCl4 treatment were subverted by MIPs administration in a dose-dependent manner. Moreover, MIPs relieved the increased hepatic malonaldehyde (MDA) and protein carbonyl (PC) content and the decreased superoxide dismutase (SOD) and catalase (CAT) contents caused by CCl4 intoxication. There was also a dose-dependent decrease in the CCl4-induced inflammatory indices, such as the levels of IL-1, IL-6, TNF-α, and myeloperoxidase (MPO), with MIPs administration. Subsequent UHPLC-MS/MS-based serum metabolomics identified 9 metabolites between the control and CCl4 groups and 10 metabolites between the HMIPs and CCl4 groups, including some critical metabolites involved in flavonoid biosynthesis, amino acid metabolism, energy metabolism, and toxicants degradation. These novel findings indicate that MIPs may be of therapeutic value in alleviating the oxidative stress and inflammation caused by CCl4. LC-MS-based metabolomics provides a valuable opportunity for identifying potential biomarkers and elucidating the protective mechanisms of medicinal mushrooms against hepatic oxidative injury.